2022
DOI: 10.3390/healthcare10030460
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Physical Activity of Seniors before and during COVID-19 Restrictions in the Czech Republic

Abstract: Social workers require a better understanding of the impact of pandemic measures on the level of physical activity of their clients to better target client activation. In this retrospective tracker-based study (two years of measurement), we examined changes in the physical activity of the elderly population (204 participants with an average age of 84.5 years) in the Czech Republic as a result of measures to prevent the spread of COVID-19. Physical activity was statistically compared according to the physical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Most studies investigating physical activity levels and related factors during the COVID-19 pandemic have used questionnaires to measure physical activity levels 36 , 37 , 38 ) . Janovsky et al reported that subjective assessments of physical activity levels might overestimate the decline in physical activity levels compared to objective assessments during the COVID-19 pandemic 39 ) . Therefore, it is highly likely that this study, which used an objective assessment method, provided an accurate assessment of physical activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies investigating physical activity levels and related factors during the COVID-19 pandemic have used questionnaires to measure physical activity levels 36 , 37 , 38 ) . Janovsky et al reported that subjective assessments of physical activity levels might overestimate the decline in physical activity levels compared to objective assessments during the COVID-19 pandemic 39 ) . Therefore, it is highly likely that this study, which used an objective assessment method, provided an accurate assessment of physical activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, a group of subjects (42%) experienced an increase in their physical activity during the pandemic when compared to the same month in the year prior [42]. A meta-analysis of 173 studies revealed that, during COVID-19 lockdowns, physical activity decreased and sedentary behavior increased at the same time [43]. Another study from South Africa showed that moderate to high levels of physical activity may have significant benefits especially in preventing negative outcomes of COVID-19, such as hospitalization, ICU admission, ventilation and death [44].…”
Section: Discussionmentioning
confidence: 99%
“…The oldest app in the dataset was released on September 28, 2008. The description of the dataset is listed in Table 1, and the dataset is available to download on this link 3 .…”
Section: Data Collectionmentioning
confidence: 99%
“… 1 Collective trauma is defined as a significant event that negatively affects the population. 2 The pandemic declined people's physical activity as observed by Janovský et al 3 and Konda et al 4 Specifically, the pandemic hampered fitness activities in gyms and encouraged people to explore alternate fitness activities such as workouts at home, yoga, and meditation, as Kaur et al 5 discussed. Technology has played a pivotal role in maintaining H-F activities during the pandemic through mHealth (mobile health) and mobile apps.…”
Section: Introductionmentioning
confidence: 98%